Dourada, a Capela do Recife: história e patrimônio religioso católico do Recife colonial. - Pereira, Flávia de Sousa (2021)
In this work I examine the Capela Dourada do Recife, a place endowed with Catholic religious and artistic significance and an example of an eighteenth-century Pernambuco, which was built thanks to donations and with the help of the sugar aristocracy, becoming a symbol of this opulence and domination. In compliance with the legislation that governs this postgraduate program, a catalog of the Chapel will be developed as a product, thus expanding and strengthening the perception as a historical heritage and museum space. The idea arose from the needs identified in the research process and it should be noted that the proposed catalog, with photos and texts in three languages – Portuguese, English and Spanish – will be part of the action strategy that will be developed, unifying and improving the instruments communication tools that already exist there.